Canva And Wordwall Interactive Media Optimize Elementary Student Mathematics Achievement: Media Interaktif Canva Dan Wordwall Mengoptimalkan Prestasi Matematika Siswa Dasar - Nur Hasanah; Zulnuraini Zulnuraini; Nuraini Nuraini; Abdul Rahman; Ammar Abdullah Joni Guci (Academia Open, 2026)
General Background Learning instructional tools serve as crucial technological bridges for delivering educational content and stimulating student engagement in the modern digital era. Specific Background However, third-grade pupils at SDN Donggala Kodi currently demonstrate low numerical comprehension due to passive classroom participation, lack of focus, and the reliance on conventional, non-engaging instructional tools. Knowledge Gap While previous studies have independently examined visual platforms or educational games, research combining both presentation software and gamified evaluation tools to address low numerical proficiency remains limited. Aims This study investigates the application of combined digital platforms on the learning progress of third-grade pupils at SDN Donggala Kodi. Results Utilizing a pre-experimental one-group pretest-posttest design with 21 participants, data analysis revealed a significant mean score progression from 58.90 to 82.42 (p < 0.001), alongside a moderate N-Gain score of 0.3169. Novelty This research demonstrates the specific utility of integrating visual presentation capabilities with interactive game-based evaluations to actively engage pupils in learning whole numbers up to 1000. Implications These findings suggest that integrating multimedia visualization with gamified assessments provides a highly supportive and student-centered alternative pedagogical strategy for fostering fundamental numerical education. Highlights Pre-test and post-test assessments of third-grade pupils demonstrated a significant score progression from 58.90 to 82.42. The integration of visual presentations and gamified evaluations successfully stimulated active classroom participation during whole number lessons. Analytical testing confirmed a significance value below 0.001, verifying positive pedagogical consequences. Keywords Interactive Learning Media; Canva Application; Wordwall Educational Game; Mathematics Learning Outcomes; Elementary School Education